Analisis Dampak Game Online Mobile Legend Pada Anak Usia Sekolah Dasar Di Desa Junjung Kecamatan Sumbergempol Kabupaten Tulungagung - Nugrananda Janttaka (Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to describe and analyze the impact of legendary online mobile games on elementary school age children in the village of Junjung, Sumbergempol. To achieve these objectives used educational research with qualitative research types with phenomenological research approaches. The instrument used are document, interview and observation.The results of the analysis of the research data above show that the children who have problems caused by the legendary Mobile online game are BI, BA, FE and NA, they all meet all of these indicators because they are 4 who often play the Mobile Legend online game,has no interaction with peers and neighbours, they have a physchological disorder anad mental illness. The Positive impact of online game are got to know of tecnologhy, understand rules of technologhy, increase motoric and new vocabulary in English.